Factors Determining Promotional and Image-Building Activities of Vocational Schools - Widelska Urszula (Marketing of Scientific and Research Organizations)
This study investigates the factors influencing the promotion and image-building activities of vocational schools in Poland, with a focus on the Podlaskie Voivodeship (one of Poland’s fifteen regions). Using structural analysis and the MICMAC methodology, the research identifies key variables shaping vocational education promotion, including external factors like competition in the education market, generational attitudes of students, and regional economic development, as well as internal factors such as schools’ initiative-taking capacity, awareness of promotional needs, and relationships with employers. Expert stakeholder evaluations are analyzed using a structured methodology, ensuring that identified factors and relationships reflect insights from professionals and stakeholders in the vocational education sector. Significant interdependencies were found among factors, emphasizing the pivotal role of relationships with employers and the adaptive use of social media as a goal-oriented tool for communication. Findings underscore that effective promotion of vocational education requires a strategic approach integrating internal strengths with external collaborations to address stakeholder needs, improve societal perception, and enhance competitiveness. Key recommendations include fostering relational capital, involving employers in defining school missions, and aligning promotional strategies with dynamic labor market demands and technological advancements.